Access to the urban national park in Cape Town: Where urban and natural environment meet. (October 2016) - Donaldson, Ronnie; Ferreira, Sanette; Didier, Sophie; Rodary, Estienne; Swanepoel, Janie
Abstract: This paper reveals the relational, multi-layered constructions and boundaries of park spaces and who the users of the Table Mountain National Park (TMNP) in Cape Town are. Access to TMNP is discussed within its urban metropolitan context and the role Table Mountain has played in Capetonians representations of the mountain through different eras – the colonial, apartheid and post-apartheid. The formidable challenge to the park management, with visitor numbers of around 3 million annually, is to provide a high-quality recreational and tourist experience without compromising the ecological integrity of the park and making sure that the park is accessible to all. However, the December 2007 to November 2008 TMNP survey found that the park is a recreational space for the affluent. Most visitors to the park are from high-income neighbouring suburbs. Issues of use of and access to the park by visitors vary greatly and typically reflect the duality of the legacy of apartheid planning. If most of the South African population is largely invisible in the TMNP (and other national parks), questions arise about the parks' future relevance, meaning, and protection. Highlights: Major marketing promotions of the city portray Table Mountain as the defining landmark and spatial anchor of Cape Town. Table Mountain as a symbolic representation of the broader TMNP landscape. Colonial and apartheid park use exclusions are entrenched in contemporary socio-spatial ordering of the city. Table Mountain National Park is almost exclusively used by residents living in high-income suburbs. 'Non-white' Cape Town residents mainly visit the touristic sites implying they are merely 'tourists' in their own city.